Marketing Analisys of Localchicken Egg (Gallus Domesticus) in Pematangsiantar, North Sumatera - Rendell Herbert Ginting; Armyn Hakim Daulay; Nevy Diana Hanafi (Indonesian Journal of Agricultural Research)
Abstract. The purpose of this research was to analyze the marketing system and marketing channel of chicken eggs and to analyze marketing efficiency based on marketing margin, price share and profit ratio of chicken egg cost in Pematangsiantar Municipality of Simalungun District. This research was conducted for two months, from July to August 2017. The methods used in data collection were: sampling of breeders and other marketing institutions selected by snowballing sampling technique and data collection methods was done by interviewing techniques using questionnaire. Data analysis included: marketing costs, marketing margin,farmer share and profit cost ratio of each marketing channel. The results of this study indicated that there were four marketing channels. The marketing margin on the Channel II showed the smallest cost margin and the largest profit margin so that it showed the largest cost-benefit ratio. The largest farmer share was obtained on the Channel IV but this channel  used only the retailers as an intermediate channel (one level) and relatively few exchanged eggs. So it was concluded that the Channel II was the most efficient channel becauseof the smallest cost and that the  profits were spread evenly among all the marketing institutions that play a role. The need for chicken eggs in Pematangsiantar Municipality was supplied from outside the city (63.33%) and filled by breeders from within the city(36.66%).